Characterization of Outdoor to Indoor Propagation in Urban Area by Using A Combination of COST231 Walfisch-Ikegami and COST231 Multiwall Models in 1800 Mhz and 2100 Mhz - Pinem, Maksum; Zulfin, Muhammad; Suherman, S; M. Sihombing, Panangian; Indah Rezkika, Sri (International Journal of Engineering and Technology, 2018)
Increasing numbers of the mobile communication users in urban city; especially indoor users cause the radio coverage prediction of outdoor to indoor becoming important. Obstacles are the main problems for outdoor to indoor propagation that weaken signal level and worsen information detection. This paper proposes a combination of COST231 Walfisch-Ikegami and COST231 Multiwall to predict the received signal. By comparing the predicted and the measured signal level in the Antara building, Medan city for both 1800 MHz and 2100 MHz channels, the proposed model outperforms the compared method in predicting signal level. The proposed model is able to suppress the prediction deviation 11.035 dB lower than the compared method for Sector A and 5.98 dB lower at Sector B.Â Â